Stress adaptation disorders play a role in rat gestational diabetes with oxidative stress and glucose transporter-4 expression. (1st September 2020) - Feng, Yan; Feng, Qi; Yin, Shaohua; Xu, Xiaomeng; Song, Xinna; Qu, Hongmei; Hu, Jianwei
Abstract: Stress adaptation disorder exists in gestational diabetes mellitus (GDM) women, this study was to investigate the impact of stress adaptation disorder on glucose disposal and skeletal muscle glucose transporter4 (GLUT4) expression in GDM rat model. Rats were assigned randomly to Normal control (NC) group and GDM group. We analyzed the levels of corticosterone, epinephrine (E), norepinephrine (NE), malondialdehyde (MDA) and superoxide dismutase (SOD), interleukin-6 (IL-6) and expression of GLUT4 were also detected. Homeostasis model assessment (HOMA-IR) was used to evaluate insulin resistance. Compared with NC group, E, NE and Corticosterone were increased significantly, SOD and MDA were higher and GLUT4 expression was significantly lower in GDM rats. Corticosterone was positively related to MDA, MDA was positively and SOD was negatively related to HOMA-IR in both groups, IL-6 showed significant positive correlations with HOMA-IR. NE and Corticosterone were negative related to GLUT4 in GDM group. Stress hormones (E, NE and Corticosterone), MDA and IL-6 were the risk factors of GDM, SOD was the protective factor of GDM. Changes of stress hormones indicate that stress adaptation disorder exists in GDM rats. Stress adaptation disorder increase oxidative stress injury and inflammation, decrease GLUT4 and lead to incline of glucose uptake, result in hyperglycemia. Gaining an insight into correlations of these changes may be beneficial to maternal and child health and is important for the prevention of glycemia-related diseases.